Method for enhancing degradation of organic pollutants by using acid-modified hydrothermal carbon

By introducing an inorganic acid solution during the preparation of hydrothermal carbon for acid modification, the surface functional groups and pore structure of hydrothermal carbon is improved, and the problem of insufficient Fe(III)/Fe(II) cycle efficiency is solved, which significantly improves the The degradation efficiency of the iron salt and persulfate system on organic pollutants has achieved efficient and economical pollutant removal.

CN119503998AActive Publication Date: 2025-02-25GUANGDONG UNIV OF PETROCHEMICAL TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411801571.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-25
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In the prior art, Fe(III)/Fe(II) cycle efficiency is insufficient, resulting in low degradation efficiency of iron salt and persulfate degradation systems on organic pollutants, large catalyst usage, high treatment cost, and difficult to achieve in water. Efficient removal of organic pollutants.

Method used

In the degradation system constructed by acid-modified hydrothermal carbon, the surface content of hydrothermal carbon is improved by using inorganic acid solutions (such as sulfuric acid, nitric acid, hydrochloric acid) during the hydrothermal carbonization process. Oxygen functional groups, pore structure and specific surface area, thereby significantly enhancing Fe(III)/Fe(II) cycle efficiency.

Benefits of technology

The concentration of active species in the iron salt/persulfate oxidation system has been significantly improved, the degradation effect on organic pollutants has been enhanced, the catalyst usage and treatment cost has been reduced, the Fe(III) precipitation has been reduced, and organic pollution in water has been achieved. Efficient removal of objects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503998A_ABST
    Figure CN119503998A_ABST
Patent Text Reader

Abstract

The invention discloses a method for enhancing degradation of organic pollutants by using acid-modified hydrothermal carbon, which comprises the following steps: adding acid-modified hydrothermal carbon into a degradation system constructed by ferric salt and persulfate to degrade the organic pollutants in a water body, wherein the acid-modified hydrothermal carbon is prepared by taking biomass and an inorganic acid solution as raw materials and carrying out hydrothermal carbonization treatment. In the method disclosed by the invention, the adopted acid modified biochar has the advantages of rich surface oxygen-containing functional groups, multiple reducing components, rich pore structure, large pore diameter, large specific surface area and the like, shows very excellent adsorption capacity and catalytic reduction capacity on specific pollutants and Fe (III), and can obviously enhance the Fe (III) / Fe (II) circulation effect in a system; different types of organic pollutants in different environment media can be efficiently removed, the utilization rate of ferric salt can be remarkably increased, the treatment cost can be reduced, Fe (III) flocculent precipitation can be remarkably reduced, and the method is more environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental pollution remediation and relates to a method for enhancing the degradation of organic pollutants by utilizing acid-modified hydrothermal carbon. Background Art

[0002] Advanced oxidation technology based on persulfate has the advantages of being economical, efficient, environmentally friendly, safe and stable, and has received extensive attention in water treatment. Persulfate can be activated by energy input (ultrasound, heat, microwave), catalyst addition and other methods to produce highly active species, including sulfate radicals, hydroxyl radicals, singlet oxygen, high-valent metals, electron transfer, etc., which can then be used to degrade target pollutants. Among the catalysts used to activate persulfate, homogeneous transition metal ions, such as Co(Ⅱ), show very excellent activation performance, but they have high ecotoxicity and are prone to secondary pollution. As an alternative catalyst, iron has the advantages of being abundant on the surface, low cost, environmentally friendly, good catalytic activation effect, and no secondary pollution risk. It has become the most studied activation material and has received much attention and been widely studied in the catalytic activation of persulfate. However, existing studies have found that Fe(Ⅱ) will be consumed and rapidly oxidized to Fe(Ⅲ) during the catalytic activation of persulfate, while Fe(Ⅲ) has a weak ability to activate persulfate, which will reduce the degradation efficiency of the constructed system for organic pollutants. At the same time, the accumulated Fe(III) will also lead to the production of iron precipitation under neutral alkaline conditions, which can easily increase the treatment cost.

[0003] In order to meet the above challenges, researchers have carried out a lot of work to enhance the Fe(III) / Fe(II) cycle. For example, inorganic homogeneous reductants (such as hydroxylamine and sulfite), metal-based reductants, ultraviolet light, etc. are used to accelerate the Fe(III) / Fe(II) cycle. However, the use of inorganic homogeneous reductants (such as hydroxylamine and sulfite) has problems such as additional chemical oxygen demand, introduction of ecotoxicity, high reagent cost, and difficulty in recovery and recycling; metal-based reductants have metal dissolution, which is easy to cause secondary pollution; ultraviolet light consumes a lot of energy and has low reduction efficiency. In addition, carbon materials, such as carbon nanotubes, graphene, and biochar, can also promote the Fe(III) / Fe(II) cycle, but the cost of carbon nanotubes and graphene reagents is high, the preparation temperature of biochar is high, the product yield is low, and the ability to reduce and regenerate Fe(II) is weak. Compared with biochar prepared by pyrolysis, hydrochar has less carbon content and lower aromatization degree, but it has more oxygen-containing functional groups than biochar, and it can be directly processed without drying the wet biochar. Therefore, hydrothermal carbonization technology is often used as a pretreatment process for the preparation of high-performance biochar. Moreover, hydrochar is a new type of carbonaceous material obtained by hydrothermal carbonization of biomass / biowaste, which can also promote Fe(III) / Fe(II) cycle. However, hydrochar prepared by conventional methods still has the disadvantages of low surface oxygen-containing functional groups, small porosity and specific surface area, resulting in its adsorption capacity and reduction capacity to be further improved, and it is difficult to strengthen the Fe(III) / Fe(II) cycle in the system, which ultimately makes it difficult for the degradation system to efficiently remove organic pollutants. There are still defects such as large catalyst dosage and low degradation efficiency, which is not conducive to reducing treatment costs and achieving efficient removal of organic pollutants in water bodies. Therefore, how to obtain a catalyst with excellent adsorption and reduction capacity for Fe(III) is of great significance for achieving efficient degradation of organic pollutants in water bodies. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for enhancing the degradation of organic pollutants using acid-modified hydrothermal carbon, which can significantly enhance the Fe(III) / Fe(II) cycle efficiency under the condition of a small amount of acid-modified hydrothermal carbon, thereby significantly improving the degradation effect of the iron salt and persulfate degradation system on organic pollutants.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for enhanced degradation of organic pollutants using acid-modified hydrothermal carbon, the method comprising adding acid-modified hydrothermal carbon to a degradation system constructed of iron salt and persulfate to degrade organic pollutants in water; the acid-modified hydrothermal carbon is prepared by using biomass and inorganic acid solution as raw materials through hydrothermal carbonization treatment.

[0006] The above method is further improved in that the inorganic acid solution is one of a sulfuric acid solution, a nitric acid solution and a hydrochloric acid solution.

[0007] The above method is further improved, wherein the concentration of the sulfuric acid solution is 0.01 M to 0.5 M; the concentration of the nitric acid solution is 0.01 M to 0.15 M; and the concentration of the hydrochloric acid solution is 0.01 M to 0.15 M.

[0008] The above method is further improved, and the preparation method of the acid-modified hydrothermal carbon comprises the following steps: S1. Mixing the biomass with the inorganic acid solution and stirring to obtain a biomass mixed suspension; S2. Performing hydrothermal carbonization on the biomass mixed suspension obtained in step S1 to obtain acid-modified hydrothermal carbon.

[0009] The above method is further improved, in step S1, the mass volume ratio of the biomass to the inorganic acid solution is 1 g: 5 mL to 100 mL; the biomass is one of coconut fiber, corn stalks, sawdust, rice stalks, banana peels, fruit shells, etc.; the stirring time is 20 min to 60 min.

[0010] The above method is further improved, in step S2, the hydrothermal carbonization treatment is carried out in a high-pressure reactor; the temperature of the hydrothermal carbonization treatment is 140°C to 200°C; and the time of the hydrothermal carbonization treatment is 6 hours to 24 hours.

[0011] The above method is further improved, wherein after the hydrothermal carbonization treatment is completed, the following treatment is also included: adjusting the pH value of the product solution, filtering, washing and drying; the washing is to use water and ethanol to wash the filtered precipitate in sequence; the drying temperature is 60°C to 105°C.

[0012] The above method is further improved by adding acid-modified hydrothermal carbon to the degradation system constructed by iron salt and persulfate to degrade organic pollutants in the water body, comprising the following steps: mixing the acid-modified hydrothermal carbon, iron salt, persulfate and organic pollutant wastewater for oxidative degradation reaction to complete the degradation of organic pollutants in the wastewater; the amount of the acid-modified hydrothermal carbon added is 0.05 g to 0.3 g per liter of the organic pollutant wastewater.

[0013] The above method is further improved in that the amount of iron salt added is 0.05 mmol to 0.5 mmol per liter of organic pollutant wastewater.

[0014] The above method is further improved, wherein the iron salt is a ferric salt or a divalent iron salt; the ferric salt is at least one of ferrous sulfate, ferric chloride, ferric nitrate, and ferrous acetate; the divalent iron salt is at least one of ferrous sulfate heptahydrate, ferrous chloride, ferrous nitrate, and ammonium ferrous sulfate.

[0015] The above method is further improved in that the amount of persulfate added is 0.2 mmol to 1.0 mmol per liter of organic pollutant wastewater.

[0016] The above method is further improved, wherein the persulfate is peroxymonosulfate and / or peroxydisulfate; the peroxymonosulfate is potassium peroxymonosulfate; the peroxydisulfate is at least one of sodium persulfate, potassium persulfate, and ammonium persulfate.

[0017] The above method is further improved, wherein the organic pollutant in the organic pollutant wastewater is at least one of benzoic acid, tetracycline, phenol, bisphenol A or sulfamethoxazole; and the initial concentration of the organic pollutant in the organic pollutant wastewater is 5 μmol / L to 40 μmol / L.

[0018] The above method is further improved in that the initial pH value of the control system during the oxidative degradation reaction is 3 to 9; the temperature of the oxidative degradation reaction is 20°C to 50°C; the oxidative degradation reaction is carried out under stirring conditions with a rotation speed of 100 rpm to 250 rpm; and the time of the oxidative degradation reaction is 10 min to 30 min.

[0019] Compared with the prior art, the advantages of the present invention are: (1) In view of the shortcomings of hydrothermal carbon, such as a small number of surface oxygen-containing functional groups, a small number of reducing components, a small porosity and a small specific surface area, and the resulting defects of hydrothermal carbon such as poor adsorption capacity and reduction capacity for Fe(III), the present invention creatively proposes a method for enhancing the degradation of organic pollutants using acid-modified hydrothermal carbon. Acid-modified hydrothermal carbon is added to a degradation system constructed by iron salt and persulfate to degrade organic pollutants in water. The acid-modified hydrothermal carbon used is prepared by hydrothermal carbonization treatment of biomass and inorganic acid solution as raw materials. Compared with the conventional hydrothermal carbonization method, the hydrothermal carbonization of biomass under acidic conditions in the present invention has the following advantages: (a) under the action of inorganic acid-assisted hydrothermal carbonization, the organic matter in the biomass will form more functional groups (such as carboxyl, amino, phenolic hydroxyl, etc.) during the hydrothermal carbonization process and expose them on the surface of the hydrothermal carbon. Compared with pore electrostatic adsorption, these functional groups have stronger adsorption selectivity and higher adsorption stability, thereby having stronger adsorption of characteristic pollutants and Fe(III), so that more Fe(III) can be reduced to Fe(II), which is beneficial to improving the regeneration efficiency of Fe(II); (b) under the action of inorganic acid-assisted hydrothermal carbonization, the hydrothermal carbonization reaction can be promoted, so that more biomass can be converted into hydrothermal carbon. At the same time, under the action of acidic ions, the pore structure of the hydrothermal carbon can be effectively improved, the surface area and pore diameter of the hydrothermal carbon can be significantly increased, and the hydrothermal carbon can be remarkably increased. It can change the structural defects, thereby exposing more adsorption sites and active sites, which can not only improve the adsorption capacity of hydrothermal carbon for characteristic pollutants and Fe(III), but also improve the catalytic reduction ability of hydrothermal carbon for Fe(III), making the regeneration efficiency of Fe(II) higher, promoting the Fe(III) / Fe(II) cycle in the system, and having a better effect on the degradation of organic pollutants in the construction system; (c) The biomass components can decompose at a lower temperature, undergo hydrolysis and dehydration, and undergo aldol condensation reaction, cycloaddition reaction, aromatization reaction and polymerization to form carbon-rich solid products. Moreover, these reactions are further enhanced under the action of inorganic acid-assisted hydrothermal carbonization, which can not only activate the hydrothermal carbon surface and increase the number of surface active sites, but also oxidize some unstable functional groups, which is beneficial to increase the content of reducing components, making the hydrothermal carbon exhibit more excellent reduction performance.In the method of the present invention, the acid-modified biochar used has the advantages of rich surface oxygen-containing functional groups, many reducing components, rich pore structure and large pore size, large specific surface area, etc., and shows very excellent adsorption capacity for characteristic pollutants and Fe(III), especially, it shows very excellent catalytic reduction ability for Fe(III). Therefore, adding acid-modified hydrothermal carbon to the degradation system constructed by iron salt and persulfate can significantly enhance the circulation effect of Fe(III) / Fe(II) in the system. On the one hand, the concentration of active species in the iron salt / permonosulfate oxidation system can be significantly increased, so as to better construct a free radical / non-free radical coexistence oxidation system dominated by high-concentration sulfate radicals and high-valent iron, so that the above-mentioned free radical / non-free radical coexistence oxidation system can be used to efficiently remove different types of organic pollutants in different environmental media. On the other hand, the utilization rate of iron salt can also be significantly improved, which is conducive to reducing treatment costs, and significantly reducing Fe(III) flocculation precipitation, which is more green and environmentally friendly.

[0020] (2) In the present invention, the inorganic acid solution used is one of sulfuric acid solution, nitric acid solution and hydrochloric acid solution. At the same time, the concentration of sulfuric acid solution is 0.01M-0.5M, the concentration of nitric acid solution is 0.01M-0.15M, and the concentration of hydrochloric acid solution is 0.01M-0.15M. By optimizing the type and concentration of the acidic solution, the adsorption sites and catalytic active sites on the surface of hydrothermal carbon can be significantly increased while increasing the biochar yield, thereby obtaining acid-modified hydrothermal carbon with high yield and excellent performance. In particular, when the concentration of the inorganic acid solution is too low, the oxygen-containing functional groups on the surface of the hydrothermal carbon do not increase much, and the enhancement effect on Fe(III) adsorption and reduction is not significant, making it difficult to promote the degradation effect of the system on organic pollutants. At the same time, when the concentration of the inorganic acid solution exceeds 0.5 M, the hydrothermal carbon can be completely corroded in the hydrothermal reaction, causing the corresponding modified hydrothermal carbon to be completely dissolved. For example, when the concentration of nitric acid and hydrochloric acid reaches 0.5 M, the material obtained by the hydrothermal carbonization reaction is completely dissolved and no solid product can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0021] Figure 1 This is a diagram showing the degradation effect of sulfamethoxazole by the Fe(III) / permonosulfate system under different acid-modified hydrochar and unmodified hydrochar conditions in Example 1 of the present invention.

[0022] Figure 2 This is a graph showing the degradation rate of sulfamethoxazole by the Fe(III) / permonosulfate system under different acid-modified hydrochar and unmodified hydrochar conditions in Example 1 of the present invention.

[0023] Figure 3 This is a graph showing the concentration variation of Fe(III) reduced to Fe(II) in different acid-modified hydrothermal carbon / Fe(III) systems in Example 2 of the present invention.

[0024] Figure 4 Graph showing the change in Fe(II) concentration in the hydrothermal carbon / Fe(III) / permonosulfate system modified with different acids in Example 2 of the present invention.

[0025] Figure 5 Graph showing the change in Fe(III) concentration in the hydrothermal carbon / Fe(III) / permonosulfate system modified with different acids in Example 2 of the present invention.

[0026] Figure 6 This is a diagram showing the degradation effect of sulfamethoxazole on the 0.1 M nitric acid-modified hydrothermal carbon / Fe(III) / permonosulfate system under different pH conditions in Example 3 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0028] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values ​​of more than three repeated experiments.

[0029] Example 1 A method for enhancing the degradation of organic pollutants by using acid-modified hydrothermal carbon, specifically adding acid-modified hydrothermal carbon to a degradation system constructed by iron salt and persulfate to degrade sulfamethoxazole in water, comprising the following steps: Take a conical flask and carry out the degradation experiment in a 100 mL system with a sulfamethoxazole concentration of 25 μM. After adding sulfamethoxazole and the corresponding water, adjust the pH of the solution to 3.0 with 0.5 M sulfuric acid (unless otherwise specified), place it in a water bath oscillator, add acid-modified hydrochar (0.1 g / L), potassium permonosulfate complex salt PMS (0.2 mM) and iron sulfate (Fe(Ⅲ), 0.2 mM), and carry out oxidative degradation reaction at 30°C and 150 rpm for 30 min to complete the degradation of sulfamethoxazole in the water.

[0030] In this embodiment, the acid-modified hydrothermal charcoal used is prepared by hydrothermal carbonization treatment of coconut fiber and inorganic acid solution as raw materials, comprising the following steps: The separated coconut fiber raw material is washed, drained, moved to a beaker and placed in an oven to be dried completely. The dried coconut fiber raw material is then cut into small pieces and torn apart. The material is crushed thoroughly using a crusher and passed through a 100-mesh sieve to obtain coconut fiber, which is then sealed in a sealed bag and moved to a desiccator for storage.

[0031] Preparation of acid-modified hydrothermal carbon: 1 g of coconut fiber was accurately weighed with an electronic balance, added to the reactor and marked, and different types and concentrations of inorganic acid solutions (sulfuric acid solution, nitric acid solution and hydrochloric acid solution) (0.01 M, 0.1 M, 0.2 M, 0.5 M) were selected, 30 mL of each was added to different reactors, and stirred in a magnetic stirrer for 30 min to obtain a coconut fiber mixed suspension. The reactor was then assembled and placed in a 180 °C oven for hydrothermal carbonization for 12 hours. After the reaction was completed, it was cooled to room temperature and taken out. After standing and stratification, the surface oil was poured out. The material was washed with deionized water by a vacuum pump until neutral, and then placed in a vacuum drying oven at 60 °C until completely dry. After taking it out, it was ground into powder and divided into centrifuge tubes for storage and marked for later use.

[0032] Table 1 Numbers of acid-modified hydrothermal carbons prepared under different types and concentrations of inorganic acid solutions

[0033] In this example, unmodified hydrothermal carbon was also prepared by using water instead of the inorganic acid solution, and other conditions were the same.

[0034] In this example, before the HPLC analysis, 1.0 mL of sample was drawn with a syringe at specified time intervals (0, 1, 3, 5, 10, 15, 30 min), filtered with a 0.45 μm filter, quenched by adding an excess of sodium thiosulfate solution, and the concentration of sulfamethoxazole in the sample was determined, and then the degradation efficiency of sulfamethoxazole was calculated. The results are shown in FIG. Figure 1 shown.

[0035] Figure 1 The figure is a graph showing the degradation effect of sulfamethoxazole by the Fe(III) / peroxymonosulfate system under different acid-modified hydrochar and unmodified hydrochar conditions in Example 1 of the present invention. Figure 1As shown, due to the poor activation performance of unmodified hydrocharcoal on permonosulfate, the degradation efficiency of sulfamethoxazole in the system constructed by unmodified hydrocharcoal and permonosulfate within 30 minutes was only 8.4%, which was similar to the Fe(III) / permonosulfate system without hydrocharcoal. In the system of unmodified hydrocharcoal / Fe(III) / permonosulfate, the degradation efficiency of sulfamethoxazole was significantly improved to 52.0%. Compared with them, in the present invention, an inorganic acid solution is introduced during the preparation of hydrocharcoal, and the degradation performance of Fe(III) / permonosulfate system on sulfamethoxazole can be significantly improved by acid-modified hydrocharcoal. Specifically, compared with the unmodified hydrochar / Fe(III) / permonosulfate system, when the concentration of the sulfuric acid solution was 0.01 M, 0.1 M, 0.2 M and 0.5 M, respectively, the prepared sulfuric acid-modified hydrochar was added to the Fe(III) / permonosulfate system, and the degradation efficiency of sulfamethoxazole was increased to 58.0%, 61.5%, 83.0% and 67.5% respectively after 30 minutes of degradation reaction. This shows that the sulfuric acid-modified hydrochar obtained after modification with a sulfuric acid solution with a concentration of 0.01 M-0.5 M can further improve the degradation efficiency of the Fe(III) / permonosulfate system for the degradation of sulfamethoxazole. In particular, when the concentration of the sulfuric acid solution is 0.2 M, the effect of sulfuric acid-assisted modification is the best, and the obtained sulfuric acid-modified hydrochar has better adsorption capacity and catalytic reduction ability. Compared with the unmodified hydrothermal carbon / Fe(III) / permonosulfate system, when the concentration of the nitric acid solution was 0.01 M and 0.1 M, respectively, the prepared nitric acid-modified hydrothermal carbon was added to the Fe(III) / permonosulfate system, and the degradation efficiency of sulfamethoxazole was increased to 63.0% and 88.0% respectively after 30 minutes of degradation reaction. This indicates that the nitric acid-modified hydrothermal carbon obtained after modification with a nitric acid solution with a concentration of 0.01 M-0.2 M can further improve the degradation efficiency of the Fe(III) / permonosulfate system for the degradation of sulfamethoxazole. In particular, the effect of nitric acid-assisted modification is best when the concentration of the nitric acid solution is 0.1 M, and the obtained nitric acid-modified hydrothermal carbon has better adsorption capacity and catalytic reduction ability. In addition, when the concentration of nitric acid solution is further increased, the degradation performance of sulfamethoxazole by the prepared nitric acid-modified hydrochar in the system constructed with Fe(III) and peroxymonosulfate is significantly reduced. When the concentration of nitric acid solution is 0.2 M, the degradation efficiency of sulfamethoxazole by the system is only 24.0%. In particular, when the concentration of nitric acid solution is 0.5 M, the solid hydrochar sample prepared by auxiliary preparation is corroded and dissolved by acid, and the solid sample of nitric acid-modified hydrochar cannot be obtained. In addition, the degradation performance of the hydrochloric acid-modified biochar prepared by hydrochloric acid solution modification in the system constructed with Fe(III) and peroxymonosulfate is similar to that of nitric acid solution.

[0036] Figure 2 The degradation rate of sulfamethoxazole by Fe(III) / permonosulfate system under different acid-modified hydrothermal carbon and unmodified hydrothermal carbon conditions in Example 1 of the present invention is shown in Figure 1. The data of the degradation of sulfamethoxazole by Fe(III) / permonosulfate system by the above different acid-modified hydrothermal carbon and unmodified hydrothermal carbon were fitted by pseudo-first-order kinetic rate equation to obtain the degradation rate ( k obs ).like Figure 2 As shown in Figure 2, the first-order kinetic rate of degradation of sulfamethoxazole by the unmodified hydrothermal carbon / Fe(III) / permonosulfate system is 10.66×10 -2 min -1 Compared with it, the first-order kinetic rate of degradation of sulfamethoxazole by the system constructed by hydrothermal carbon modified with different acids, Fe(III) and peroxymonosulfate in this embodiment was significantly improved. Among them, the nitric acid-modified hydrothermal carbon modified by 0.1 M nitric acid solution was added to the Fe(III) / peroxymonosulfate system, which could significantly improve the degradation activity of sulfamethoxazole in the system, and the first-order kinetic rate reached 29.43×10 -2 min -1 , which is 2.8 times the degradation rate of sulfamethoxazole by the unmodified hydrothermal carbon / Fe(III) / permonosulfate system. After the sulfuric acid-modified hydrothermal carbon modified by 0.2 M sulfuric acid solution was added to the Fe(III) / permonosulfate system, the degradation activity of sulfamethoxazole by the system was significantly improved, and the first-order kinetic rate reached 25.09×10 -2 min -1 In addition, these acid-modified hydrothermal carbons enhanced the degradation rate of sulfamethoxazole by Fe(III) / peroxymonosulfate system exactly corresponding to Figure 1 The degradation kinetics of .

[0037] comprehensive Figure 1 and Figure 2 From the above, adding the acid-modified hydrothermal carbon prepared by the present invention into the Fe(III) / permonosulfate system can significantly enhance the degradation performance of the system for sulfamethoxazole, and can significantly improve the degradation rate and degradation effect of sulfamethoxazole, which is beneficial to achieve efficient removal of organic pollutants in water bodies.

[0038] Example 2 The effect of the acid-modified hydrothermal carbon prepared under different concentrations and different types of inorganic acid solutions in Example 1 of the present invention on the iron form in the Fe(III) / permonosulfate system was investigated, comprising the following steps: (1) Fe(Ⅱ) concentration detection. 2.0 mL of 1,10-phenanthroline (10 mM) and 0.4 mL of saturated sodium acetate (NaAc) solution were added to a 10 mL centrifuge tube in advance. Then, 2.6 mL of the filtered filtrate was taken at different degradation reaction time points, added to the centrifuge tube and mixed. After standing for 10 min, the absorbance of Fe(Ⅱ) was detected at a wavelength of 510 nm by ultraviolet spectrophotometry, and the concentration was calculated using the standard curve.

[0039] (2) Total Fe concentration detection. 0.8 mL of hydroxylamine hydrochloride (10 mM), 2.0 mL of 1,10-phenanthroline (10 mM) and 0.4 mL of saturated sodium acetate solution were added to a 10 mL centrifuge tube in advance. Then, 1.8 mL of the filtered filtrate was taken at different degradation reaction time points, added to the centrifuge tube and mixed and shaken. After standing for 10 min, the absorbance of Fe(Ⅱ) was detected by ultraviolet spectrophotometry at a wavelength of 510 nm and the concentration was calculated using the standard curve. The saturated sodium acetate solution acts as a buffer solution pH. The concentration of Fe(Ⅲ) in the degradation reaction is equal to the total Fe concentration minus the concentration of Fe(Ⅱ).

[0040] Figure 3 The graph is a concentration change diagram of reducing Fe(III) to Fe(II) in different acid-modified hydrothermal carbon / Fe(III) systems in Example 2 of the present invention. Figure 3 It can be seen that the unmodified hydrothermal carbon can directly and continuously reduce Fe(III) and generate 61.72 μM Fe(II) within 30 minutes. Compared with the unmodified hydrothermal carbon, the ability of the acid-modified hydrothermal carbon of the present invention to reduce Fe(III) is significantly enhanced. Among them, the nitric acid-modified hydrothermal carbon modified with a 0.1 mM nitric acid solution and the sulfuric acid-modified hydrothermal carbon modified with a 0.2 mM sulfuric acid solution, the Fe(II) concentration in the system increased to 93.10 μM and 87.83 μM respectively within 30 minutes. In addition, the nitric acid-modified hydrothermal carbon and the hydrochloric acid-modified hydrothermal carbon modified with a 0.2 mM nitric acid solution and a hydrochloric acid solution, the Fe(II) concentration in the system decreased to 44.11 μM and 20.83 μM respectively within 30 minutes. It can be seen that the amount and trend of the acid-modified hydrothermal carbon prepared under different conditions in reducing Fe(III) to Fe(II) are consistent with the results. Figure 1 and Figure 2 The degradation performance of the acid-modified hydrothermal carbon / Fe(III) / permonosulfate system constructed in the experiment is consistent with that of sulfamethoxazole.

[0041] Figure 4 Graph showing the change in Fe(II) concentration in the hydrothermal carbon / Fe(III) / permonosulfate system modified with different acids in Example 2 of the present invention.

[0042] Figure 5 Graph showing the change in Fe(III) concentration in the hydrothermal carbon / Fe(III) / permonosulfate system modified with different acids in Example 2 of the present invention.

[0043] Depend on Figure 4 and Figure 5 It can be seen that in the constructed acid-modified hydrochar / Fe(III) / permonosulfate system, the Fe(III) concentration decreased during the degradation process and the Fe(II) concentration was detected, further confirming that the acid-modified hydrochar can indeed contribute to the reduction of Fe(III). In general, the total iron concentration fluctuated slightly during the reaction of the constructed system but remained basically unchanged. It is worth noting that the Fe(II) concentration in the constructed acid-modified hydrochar / Fe(III) / permonosulfate system is much lower than the Fe(II) concentration in the hydrochar / Fe(III) system, which is attributed to the fact that the reduced Fe(II) is used to activate the permonosulfate, resulting in a significant decrease in its concentration. In addition, compared with the unmodified hydrochar / Fe(III) / permonosulfate system, the addition of acid-modified hydrochar makes the Fe(II) concentration generated in the Fe(III) / permonosulfate system higher.

[0044] Depend on Figure 3-5 It can be seen from the results in that compared with the unmodified hydrothermal carbon, the acid-modified hydrothermal carbon used in the present invention can significantly improve the degradation performance of the Fe(III) / permonosulfate system on sulfamethoxazole. Specifically, a certain concentration of inorganic acid solution assisted in the modification of hydrothermal carbon to give the hydrothermal carbon a rich functional group (including carboxyl, amino, phenolic hydroxyl) and persistent free radicals, so that it has good reduction characteristics, and can significantly promote the reduction of Fe(III) to Fe(II), provide more available Fe(II) to promote the activation of permonosulfate to produce a higher concentration of active species, and achieve enhanced degradation of organic pollutants. Moreover, with the increase of the concentration of the inorganic acid solution, the content of functional groups on the surface of the hydrothermal carbon increased significantly, resulting in an increase in the generation of active species and the degradation efficiency of organic pollutants. In addition, different types of inorganic acid solutions have different effects on the reduction characteristics of the hydrothermal carbon surface functional groups and persistent free radicals. It is worth noting that when the concentration of the inorganic acid solution is too high, the hydrothermal carbon is easily corroded by acid, resulting in a significant reduction in the quality of the hydrothermal carbon product formed by the hydrothermal carbonization reaction, or even complete dissolution, and no solid product can be obtained.

[0045] Example 3 A method for enhancing the degradation of organic pollutants by using acid-modified hydrothermal carbon, specifically investigating the applicability of a nitric acid-modified hydrothermal carbon / Fe(III) / permonosulfate system under different initial pH conditions, comprising the following steps: Take a conical flask and carry out a degradation experiment in a 100 mL system with a sulfamethoxazole concentration of 25 μM. After adding sulfamethoxazole and the corresponding water, the pH value of the solution is adjusted to 3, 5, 7, 9, and 11 with 0.5 M sulfuric acid or sodium hydroxide, respectively, and placed in a water bath oscillator. 0.1 M nitric acid-modified hydrothermal carbon (0.1 g / L), potassium permonosulfate complex salt PMS (0.2 mM) and ferrous sulfate (Fe(III), 0.2 mM) prepared in Example 1 are added, and an oxidative degradation reaction is carried out at 30° C. and 150 rpm. The reaction time is 30 min, and the degradation of sulfamethoxazole in the water is completed.

[0046] Figure 6 This is a diagram showing the degradation effect of sulfamethoxazole on the 0.1 M nitric acid-modified hydrothermal carbon / Fe(III) / permonosulfate system under different pH conditions in Example 3 of the present invention. Figure 6 In this study, 0.1 M nitric acid-modified hydrothermal carbon with the best performance was selected as the co-catalyst to study the degradation of sulfamethoxazole under different pH conditions. Figure 6 It can be obtained that, under acidic conditions or even neutral and weakly alkaline environments (pH 3-9), 0.1 M nitric acid is added to modify the hydrothermal carbon, and the degradation performance of the constructed system for sulfamethoxazole is almost the same, and the degradation rate is more than 90%, and both can achieve good degradation effects. However, at pH 11, the degradation efficiency of sulfamethoxazole is significantly reduced, only 24.10%. The reason for the decrease in the degradation effect of the constructed system under strong alkaline conditions may be that Fe(III) and its reduced Fe(II) are easily precipitated under strong alkaline conditions, reducing the available Fe(II) in the constructed system. In other words, under alkaline conditions, Fe(III) in the constructed system undergoes hydrolysis to generate iron hydroxide precipitation, resulting in a decrease in Fe(II), a decrease in catalytic activation ability, and a significant decrease in the degradation effect of sulfamethoxazole. It can be seen that the acid-modified hydrothermal carbon / Fe(III) / permonosulfate system constructed in the present invention can achieve good degradation performance in a wide range of pH 3-9.

[0047] From the above results, it can be seen that compared with the conventional method, the acid-modified biochar used in the method of the present invention has the advantages of rich surface oxygen-containing functional groups, many reducing components, rich pore structure and large pore size, large specific surface area, etc., and exhibits very excellent adsorption capacity for characteristic pollutants and Fe(III), especially, it exhibits very excellent catalytic reduction ability for Fe(III). Therefore, adding acid-modified hydrothermal carbon to the degradation system constructed by iron salt and persulfate can significantly enhance the circulation effect of Fe(III) / Fe(II) in the system. On the one hand, the concentration of active species in the iron salt / persulfate oxidation system can be significantly increased to better construct a free radical / non-free radical coexistence oxidation system dominated by high-concentration sulfate radicals and high-valent iron, so that the above-mentioned free radical / non-free radical coexistence oxidation system can be used to efficiently remove different types of organic pollutants in different environmental media. On the other hand, the utilization rate of iron salt can also be significantly improved, which is conducive to reducing treatment costs, and significantly reducing Fe(III) flocculation precipitation, which is more green and environmentally friendly.

[0048] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for enhancing the degradation of organic pollutants using acid-modified hydrothermal carbon, characterized in that: The method comprises adding acid-modified hydrothermal carbon into a degradation system constructed by iron salt and persulfate to degrade organic pollutants in water; the acid-modified hydrothermal carbon is prepared by using biomass and inorganic acid solution as raw materials through hydrothermal carbonization treatment.

2. The method according to claim 1, characterized in that The inorganic acid solution is one of a sulfuric acid solution, a nitric acid solution and a hydrochloric acid solution.

3. The method according to claim 2, characterized in that The concentration of the sulfuric acid solution is 0.01 M to 0.5 M; the concentration of the nitric acid solution is 0.01 M to 0.15 M; and the concentration of the hydrochloric acid solution is 0.01 M to 0.15 M.

4. The method according to claim 1, characterized in that: The preparation method of the acid-modified hydrothermal carbon comprises the following steps: S1. Mixing the biomass with the inorganic acid solution and stirring to obtain a biomass mixed suspension; S2. Performing hydrothermal carbonization on the biomass mixed suspension obtained in step S1 to obtain acid-modified hydrothermal carbon.

5. The method according to claim 4, characterized in that In step S1, the mass volume ratio of the biomass to the inorganic acid solution is 1 g: 5 mL to 100 mL; the biomass is one of coconut fiber, corn stalks, sawdust, rice stalks, banana peels, fruit shells, etc.; and the stirring time is 20 min to 60 min.

6. The method according to claim 4, characterized in that In step S2, the hydrothermal carbonization treatment is carried out in a high-pressure reactor; the temperature of the hydrothermal carbonization treatment is 140° C. to 200° C.; and the time of the hydrothermal carbonization treatment is 6 hours to 24 hours.

7. The method according to claim 6, characterized in that After the hydrothermal carbonization treatment is completed, the following treatments are also included: adjusting the pH value of the product solution, filtering, washing and drying; the washing is to use water and ethanol to wash the filtered precipitate in sequence; the drying temperature is 60°C to 105°C.

8. The method according to any one of claims 1 to 6, characterized in that Acid-modified hydrothermal carbon is added to a degradation system constructed by iron salt and persulfate to degrade organic pollutants in water, comprising the following steps: acid-modified hydrothermal carbon, iron salt, persulfate and organic pollutant wastewater are mixed to carry out oxidative degradation reaction to complete the degradation of organic pollutants in the wastewater; the amount of the acid-modified hydrothermal carbon added is 0.05 g to 0.3 g per liter of the organic pollutant wastewater.

9. The method according to claim 8, characterized in that The amount of the iron salt added is 0.05 mmol to 0.5 mmol per liter of organic pollutant wastewater; the amount of the persulfate added is 0.2 mmol to 1.0 mmol per liter of organic pollutant wastewater; the iron salt is a trivalent iron salt or a divalent iron salt; the trivalent iron salt is at least one of ferrous sulfate, ferric chloride, ferrous nitrate, and ferrous acetate; the divalent iron salt is at least one of ferrous sulfate heptahydrate, ferrous chloride, ferrous nitrate, and ammonium ferrous sulfate; the persulfate is permonosulfate and or peroxydisulfate; the permonosulfate is potassium peroxymonosulfate; the peroxydisulfate is at least one of sodium persulfate, potassium persulfate, and ammonium persulfate; the organic pollutants in the organic pollutant wastewater are at least one of benzoic acid, tetracycline, phenol, bisphenol A, or sulfamethoxazole; the initial concentration of organic pollutants in the organic pollutant wastewater is 5 μmol / L to 40 μmol / L.

10. The method according to claim 8, characterized in that During the oxidative degradation reaction, the initial pH value of the system is controlled to be 3 to 9; the temperature of the oxidative degradation reaction is 20°C to 50°C; the oxidative degradation reaction is carried out under stirring conditions with a rotation speed of 100rpm to 250rpm; and the time of the oxidative degradation reaction is 10 min to 30 min.

Citation Information

Patent Citations

  • Inorganic acid catalysis hydrothermal method for preparation of bamboo biochar

    CN105935581A

  • Method of utilizing biochar for adsorbing orange II dye waste water and catalytically degrading the orange II dye waste water with persulfate

    CN106219724A

  • Method for accelerating iron circulation by using hydrothermal carbon to promote catalytic degradation of organic pollutants

    CN114057279A

  • Method for degrading levofloxacin hydrochloride in water body by activating persulfate with chicken manure biochar

    CN116514259A

  • FeOOH composite material as well as preparation method and application thereof

    CN118403611A